2014
DOI: 10.12691/ajps-2-5b-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pharmacist in Improving Health Related Quality of Life (HRQoL) in Hypertensive Pateints in Pakistan

Abstract: Health related quality of life (HRQoL) is used to measure both the present health status and the impact of health care interventions on the patients. The aim of the present study is to evaluate the improvement in health related quality of life of the hypertensive patients after pharmaceutical care provided by pharmacist in Pakistan. A repeated measure prospective intervention study was conducted at Armed Forces Institute of Cardiology, Rawalpindi, Pakistan. 286 hypertensive patients were enrolled at baseline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This finding is also compatible with results from previous studies, which showed significant value and the positive impact of pharmacists on the QoL among older adult patients in rural areas[ 75 ]. Moreover, a study conducted in 2014 recited a statistical improvement in the HRQoL after pharmaceutical care intervention[ 76 ]. A review supports this systematic review was carried on women with breast cancer (BC) in the Middle East countries [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is also compatible with results from previous studies, which showed significant value and the positive impact of pharmacists on the QoL among older adult patients in rural areas[ 75 ]. Moreover, a study conducted in 2014 recited a statistical improvement in the HRQoL after pharmaceutical care intervention[ 76 ]. A review supports this systematic review was carried on women with breast cancer (BC) in the Middle East countries [ 77 ].…”
Section: Discussionmentioning
confidence: 99%